If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4s + -6) + -12 = -2(6s + 5) + -2 Reorder the terms: -2(-6 + 4s) + -12 = -2(6s + 5) + -2 (-6 * -2 + 4s * -2) + -12 = -2(6s + 5) + -2 (12 + -8s) + -12 = -2(6s + 5) + -2 Reorder the terms: 12 + -12 + -8s = -2(6s + 5) + -2 Combine like terms: 12 + -12 = 0 0 + -8s = -2(6s + 5) + -2 -8s = -2(6s + 5) + -2 Reorder the terms: -8s = -2(5 + 6s) + -2 -8s = (5 * -2 + 6s * -2) + -2 -8s = (-10 + -12s) + -2 Reorder the terms: -8s = -10 + -2 + -12s Combine like terms: -10 + -2 = -12 -8s = -12 + -12s Solving -8s = -12 + -12s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '12s' to each side of the equation. -8s + 12s = -12 + -12s + 12s Combine like terms: -8s + 12s = 4s 4s = -12 + -12s + 12s Combine like terms: -12s + 12s = 0 4s = -12 + 0 4s = -12 Divide each side by '4'. s = -3 Simplifying s = -3
| -3(3s-4)-12=-2(8s+10)-2 | | (4x-5)(2x-3)= | | 5x+5=(x-23) | | -18t^4+9t^3+2t= | | .6w-.3w+.2w=3 | | 7y-9y=16 | | 15x-23x=1/3 | | (10b-3)-3(3b+1)=-6 | | f(x)=-7*x^2+5*x+7 | | -2x-10=6x+30-12 | | 2k+6=8k-20+38 | | y=-3/5+3 | | -3/5+3 | | 16=10+32x-16x^2 | | 1454-16x^2=0 | | (x+1)(x+9)-(x-3)(x+5)= | | 1/4x+5/4=9 | | -2.7x^2+35x-3=0 | | 6x+20=8x+4 | | -2.7x^2+35x+3=0 | | 3x+33y=-24 | | 5x+19=8x+7 | | 9+16/4+5*6 | | 19+5-8*4/2 | | 9/10+y/7 | | 9/10+y/1 | | 24/12+5*7 | | -25/8*64/9 | | b/a=15 | | -4(-4v-u)-5(-6u+3v)= | | -31/8*71/9 | | 3t-10=-20/t |